Untargeted metabolomics to evaluate antifungal mechanism: a study of Cophinforma mamane and Candida albicans interaction - Triastuti, Asih (2023)
Microbial interactions between filamentous fungi and yeast are still not fully understood. To evaluate a potential antifungal activity of a filamentous fungus while highlighting metabolomic changes, co-cultures between an endophytic strain of Cophinforma mamane (CM) and Candida albicans (CA) were performed. The liquid cultures were incubated under static conditions and metabolite alterations during the course were investigated by ultra-performance liquid chromatography–tandem mass spectrophotometry (UPLC–MS/MS). Results were analyzed using MS-DIAL, MS-FINDER, METLIN, Xcalibur, SciFinder, and MetaboAnalyst metabolomics platforms. The metabolites associated with catabolic processes, including the metabolism of branched-chain amino acids, carnitine, and phospholipids were upregulated both in the mono and co-cultures, indicating fungal adaptability to environmental stress. Several metabolites, including C20 sphinganine 1-phosphate, myo-inositol, farnesol, gamma-undecalactone, folinic acid, palmitoleic acid, and MG (12:/0:0/0:0) were not produced by CA during co-culture with CM, demonstrating the antifungal mechanism of CM. Our results highlight the crucial roles of metabolomics studies to provide essential information regarding the antifungal mechanism of C. mamane against C. albicans, especially when the lost/undetected metabolites are involved in fungal survival and pathogenicity.